2012
DOI: 10.5005/jp-journals-10005-1130
|View full text |Cite
|
Sign up to set email alerts
|

Dental Survey of Institutionalized Children with Autistic Disorder

Abstract: The objective of this study was to assess the oral hygiene practices, dietary pattern, dental caries status and needs of institutionalized autistic children. The sample consisted of 35 children (28 males and 7 females) in the age group of 5 to 10 years from two institutions in Maharashtra, India. The parents of the children were interviewed regarding oral hygiene practices of their respective ward and instructed to maintain a 4-day diet chart for their children. A clinical examination was conducted using WHO d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…This was not clear as it’s not detailed in the paper, but it included the same population of exactly the same age. DMFT and dmft were different but because of duplicate sampling, even if not the same dataset, we excluded.Chadha et al, 2012 [37]No comparison groupBakarcic et al, 2009 [38]Not all children in the study population have a learning disabilityFahlvik-Planefeldt et al, 2001 [39]Index for caries recording/detection system not specified, no DMFT/dmft dataFuertes-Gonzales et al, 2014 [40]This study included adults (age range 2–37 years) and did not allow for extraction of age groups.Fung et al, 2008 [41]Data collection through questionnaire (no clinical examination carried out)Lowe et al, 1985 [42]This study included adults (age range 3–30 years) and did not allow for extraction of age groups.Macho et al, 2013 [43]This study included adults (age range 2–26 years) and did not allow for extraction of age groups.Mattila et al, 2001 [44]No learning disabled children in the study population.Oredugba et al, 2007 [45]This study included adults and did not allow for extraction of age groups for DMFT/dmft indicesPollard et al, 1992 [46]No learning disabled children in the study population.Purohit et al, 2010 [47]Not all children in the study population have a learning disabilityRadha et al, 2016 [48]Errors in study authors’ conclusions from dataset: Table 10 shows CLD to have a lower caries experience than CNLD group, however the discussion and conclusion sections state the opposite to be true.Rai et al, 2012 [50]Index for caries recording/detection system not specified, no DMFT/dmft dataRekha et al 2012 [51]No DMFT/dmft data given, only caries prevalenceRuiz et al, 2018 [52]This study included adults (age range 4–20 years) and did not allow for extraction of age groups.Sarnat et al, 2016 [53]Index for caries recording/detection system not specified, no DMFT/dmft dataShaw et al, 1985 [54]Dataset includes disabled children from a very wide group also no consistency between children’s ages in the study group and control group.Suhaib et al, 2017 [55]No quantifiable measure of DMFT/dmft - descriptive only.Subramanium et al, 2011 [56]No comparison groupWeckwerth et al, 2016 […”
Section: Resultsmentioning
confidence: 99%
“…This was not clear as it’s not detailed in the paper, but it included the same population of exactly the same age. DMFT and dmft were different but because of duplicate sampling, even if not the same dataset, we excluded.Chadha et al, 2012 [37]No comparison groupBakarcic et al, 2009 [38]Not all children in the study population have a learning disabilityFahlvik-Planefeldt et al, 2001 [39]Index for caries recording/detection system not specified, no DMFT/dmft dataFuertes-Gonzales et al, 2014 [40]This study included adults (age range 2–37 years) and did not allow for extraction of age groups.Fung et al, 2008 [41]Data collection through questionnaire (no clinical examination carried out)Lowe et al, 1985 [42]This study included adults (age range 3–30 years) and did not allow for extraction of age groups.Macho et al, 2013 [43]This study included adults (age range 2–26 years) and did not allow for extraction of age groups.Mattila et al, 2001 [44]No learning disabled children in the study population.Oredugba et al, 2007 [45]This study included adults and did not allow for extraction of age groups for DMFT/dmft indicesPollard et al, 1992 [46]No learning disabled children in the study population.Purohit et al, 2010 [47]Not all children in the study population have a learning disabilityRadha et al, 2016 [48]Errors in study authors’ conclusions from dataset: Table 10 shows CLD to have a lower caries experience than CNLD group, however the discussion and conclusion sections state the opposite to be true.Rai et al, 2012 [50]Index for caries recording/detection system not specified, no DMFT/dmft dataRekha et al 2012 [51]No DMFT/dmft data given, only caries prevalenceRuiz et al, 2018 [52]This study included adults (age range 4–20 years) and did not allow for extraction of age groups.Sarnat et al, 2016 [53]Index for caries recording/detection system not specified, no DMFT/dmft dataShaw et al, 1985 [54]Dataset includes disabled children from a very wide group also no consistency between children’s ages in the study group and control group.Suhaib et al, 2017 [55]No quantifiable measure of DMFT/dmft - descriptive only.Subramanium et al, 2011 [56]No comparison groupWeckwerth et al, 2016 […”
Section: Resultsmentioning
confidence: 99%
“…Symptoms such as repetitive behaviors, unpredictable body movements and self-injurious behavior can make oral health care difficult. [123] Several studies[456] have reported that prevalence of dental caries is high in children with autism, resulting from their selective food preferences and inability to brush and floss adequately. Recommended preventive measures, such as sealants, are intended to prevent the growth of bacteria that leads to dental caries in the pit and fissures of posterior teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Following oral examination, demonstration of brushing technique to children, parents, and teachers using audiovisual aids was done along with the distribution of oral hygiene information manuals in the form of pamphlets, CD/DVDs, etc. [ 11 12 ] Diet chart of these children was obtained and diet counseling was done on subsequent visits. [ 3 ] Parents were asked to fill the awareness and attitude questionnaire about oral hygiene practices, oral habits, medical and dental history of their child, etc.…”
Section: Methodsmentioning
confidence: 99%